A monolithic catalyst for catalytic oxidation of VOCs, a method of preparation and use thereof

CN118179529BActive Publication Date: 2026-10-16DALIAN UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410163751.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-05
Publication Date
2026-10-16
Estimated Expiration
2044-02-05

AI Technical Summary

Technical Problem

将粘性胶体与活性组分混合再将其负载在堇青石蜂窝陶瓷上的方法虽然有效,但在工业放大制备中,如何兼顾CoMn2O4活性组分催化活性与机械稳定性,同时提高活性组分负载量的涂覆方法同样也是制备该类整体式催化剂的关键问题

Benefits of technology

1.本发明通过粉末粒径与焙烧温度控制使得单一晶相CoMn2O4尖晶石晶粒尺寸更小,进一步提高了活性组分的比表面积与氧物种流动性,进而提高催化剂粉末的活性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118179529B_ABST
    Figure CN118179529B_ABST
Patent Text Reader

Abstract

The application belongs to the field of catalytic purification of atmospheric pollutants, and discloses a monolithic catalyst for catalytic oxidation of VOCs, a preparation method and application thereof. The monolithic catalyst comprises a cordierite honeycomb ceramic carrier and a cobalt-manganese composite oxide coating coated on the surface of the cordierite honeycomb ceramic carrier. The application controls the powder particle size and the calcination temperature to make the single crystal phase CoMn2O4 spinel grain size smaller, further improves the specific surface area of the active component and the oxygen species flowability, and further improves the activity of the catalyst powder. The catalyst selectivity is improved through acid etching and doping of alkali metals and rare earth metals. By coordinating three key parameters of sol viscosity, powder particle size and dispersant dosage, the slurry still maintains good activity material dispersity under appropriate viscosity, improves the mechanical stability of the coating, and also makes the coating active site distribution more uniform, prevents premature aggregation of the active component, and affects the catalytic activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of atmospheric pollutant catalytic purification technology, and relates to an integral catalyst for catalytic oxidation of VOCs, its preparation method and its application. Background Technology

[0002] Volatile organic compounds (VOCs) refer to organic liquids or compounds that can spontaneously evaporate under normal temperature and pressure. Studies have shown that VOCs are currently the main controlling factor for O3 formation in key areas. Compared to the control of particulate matter, sulfur dioxide, and nitrogen oxides, VOCs management is weak and has become a bottleneck in atmospheric environmental management. Petrochemical, chemical, industrial coating, packaging and printing, and oil storage, transportation, and sales industries are key sources of VOCs emissions in my country.

[0003] Catalytic oxidation technology has been widely used as an important means of VOCs treatment. However, the main reasons restricting its widespread application are the high overall investment cost and subsequent operation, maintenance, and replacement costs resulting from the use of precious metals such as platinum and palladium in the catalyst. Since the reactivity of commercial monolithic catalysts directly affects the operating energy consumption of treatment equipment, and the strength of the catalyst coating directly affects its service life, obtaining high reactivity and long lifespan at low cost has become a current research focus.

[0004] To reduce the amount of precious metals used while improving the overall catalytic oxidation performance of the catalyst, researchers have used inexpensive transition metals such as Co, Mn, and Ce as the main active components and supported them on cordierite honeycomb ceramics to prepare novel monolithic catalysts. Zhao et al. prepared a monolithic catalyst by impregnating cordierite honeycomb ceramics in a Co and Mn salt solution for the low-temperature effective removal of toluene and ethyl acetate (Zhao H, Wang H, Qu Z. et al. Synergistic effects in Mn-Comixed oxide supported on cordierite honeycomb for catalytic deep oxidation of VOCs, Journal of Environmental Sciences, 2022, 112, 231-243). However, this method resulted in low loading rates of active components, poor mechanical stability, and easy loss of active components during use, making it difficult to achieve a service life and activity of 15,000 h. -1 The conversion rate at industrial-grade reaction space velocity must be greater than 90%.

[0005] CoMn₂O₄ spinel is considered an effective high-activity catalytic system due to its abundant defects, large specific surface area, and high oxygen species mobility. To further improve the catalyst activity in this system, many researchers have explored acid / base treatment and metal doping of CoMn₂O₄ (Ren Y, Lei X, Wang H, et al. Enhanced catalytic performance of La-Doped CoMn₂O₄ catalysts by regulating oxygen species activity for VOCs oxidation, ACS Catalysis, 2023, 13, 8293-8306), but these efforts are all at the laboratory stage and lack scale-up industrial-scale testing and mechanical strength testing. While the method of mixing viscous colloids with active components and then loading them onto cordierite honeycomb ceramics is effective, balancing the catalytic activity and mechanical stability of the CoMn₂O₄ active component with an effective coating method to increase the loading of the active component is also a key issue in the preparation of this type of monolithic catalyst in industrial-scale production. Summary of the Invention

[0006] In view of the above problems, this invention provides a monolithic catalyst for the catalytic oxidation of VOCs and its preparation method. The active component is prepared using a two-step method. First, a CoMn2O4 catalyst powder with a spinel structure is prepared. Then, a modified CoMn2O4 catalyst powder is obtained through acid / base etching and metal doping. After obtaining a viscous colloid via a sol-gel method, a dispersing agent is added to balance the slurry loading and the dispersion of the active component. Finally, the slurry is rapidly coated onto a cordierite honeycomb ceramic support using negative pressure suction, followed by drying and calcination to obtain the monolithic catalyst. This preparation method is simple, produces a highly active catalyst, exhibits strong bonding between the active component and the support, and demonstrates good mechanical stability. It is suitable for standardized industrial catalyst preparation processes.

[0007] The technical solution of the present invention: An integral catalyst for the catalytic oxidation of VOCs includes a cordierite honeycomb ceramic support and a cobalt-manganese composite oxide coating coated on the surface of the cordierite honeycomb ceramic support; the cobalt-manganese composite oxide coating contains spinel structure active components, has a thickness of 40-50 μm, and its mass ratio with the support is between 5% and 20%, with the chemical formula CoMn2O4.

[0008] The cobalt-manganese composite oxide coating also contains one or more alkali metals and rare earth metals, which are modified on the cobalt-manganese composite oxide.

[0009] Alkali metals are one or more combinations of K, Na, Li, Rb, Cs, and Mn.

[0010] Rare earth metals are one or more combinations of La, Ce, Pr, and Nd.

[0011] If the doping alkali metal component is A and the rare earth metal component is B, then the molar ratio of (A+B) / Co / Mn doping is (0.05-0.2):1:2.

[0012] A method for preparing a monolithic catalyst for the catalytic oxidation of VOCs, characterized by comprising the following steps: (1) Mix the two precursors, Co salt and Mn salt, at a Co to Mn molar ratio of 1:2, and then thoroughly mix them in excess ethanol. After mixing, control the solid content to be 100 g / L-200 g / L. Then add the precipitant dropwise and stir thoroughly. Adjust the pH to neutral, filter out the precipitate, wash it, and dry it at 80-120℃ for 2-3 hours. Then dry it at 300-400℃. o Calcination at C for 3-5 h was used to prepare single-phase CoMn2O4 powder. (2) After acid or alkali etching treatment of single-phase CoMn2O4 powder, metal doping modification is performed, and after drying and calcination, modified CoMn2O4 catalyst powder containing one or more alkali metals and rare earth metals is prepared. (3) The modified CoMn2O4 catalyst powder, dispersant and sol are mixed in a mass ratio of (10-25):(0.5-3):(72-89.5) to prepare the final coating slurry. The mixed slurry is coated onto the overall carrier by negative pressure suction, and then dried and calcined to obtain the desired monolithic catalyst.

[0013] The drying conditions for the single-phase CoMn2O4 powder are 80-120℃, and the calcination temperature is 300-400℃. o C, After calcination, the powder particle size is controlled below 300 μm, and the median diameter D 50 Any value between 50-100μm; Optionally, the acid solution is selected from sulfuric acid solution, nitric acid solution, hydrochloric acid solution, and oxalic acid solution, and the alkali solution is selected from sodium hydroxide solution and potassium hydroxide solution. The concentration of the acid or alkali solution is 0.1-30 mol / L, and the treatment time is 0.5-3 h. The modified CoMn2O4 catalyst powder has a particle size controlled below 300 μm and a median diameter D. 50 It can be any value between 50 and 100 μm.

[0014] In step (1), the Co salt precursor is one of cobalt acetate, cobalt nitrate, and cobalt chloride; the Mn salt precursor is one of manganese nitrate and manganese acetate. The precipitant is one of oxalic acid, aluminum hydroxide, and sodium carbonate.

[0015] The colloid is a pseudoboehmite sol, silica sol, silica-alumina sol, or phospho-alumina sol. The preparation steps of the sol are as follows: add sol powder to deionized water and stir for 5-30 min; the mass ratio of sol powder to water is 0.05-0.25:1 to obtain liquid A; add 1 mol / L concentrated nitric acid to deionized water and stir to mix thoroughly to obtain liquid B; the mass ratio of nitric acid to water is 0.15-0.5; mix liquids A and B at a mass ratio of 0.2-0.6:1, and let stand for 0.5-24 h to obtain the desired sol.

[0016] Modified CoMn2O4 catalyst powder was added to the prepared sol, with a solid content of 10-25 wt%, and the concentration was 20-80%. o Mix evenly under C conditions for 0.5-6 h.

[0017] The dispersing agent is either a CTAB cationic surfactant or a P123 nonionic surfactant, and its dosage is 0.5-3 wt% of the total coating slurry.

[0018] The coating method is specifically implemented as follows: the lower half of the cordierite honeycomb ceramic is immersed in the coating slurry, and uniform suction coating is performed above it using negative pressure. The suction pressure is 0.02-0.04 MPa, and the number of suctions is any value between 1 and 5.

[0019] The coated monolithic catalyst is dried at 80-120℃ for 1-2 hours and calcined at 400-500℃. o C, calcination time 3-5 h.

[0020] The monolithic catalyst is added to a fixed-bed reactor, using toluene, xylene, acetone, and / or ethyl acetate as reactant gases; preferably, the reaction volume hourly space velocity (VHSV) is 5000-25000 h⁻¹. -1 The reaction pressure is controlled at 0.1-1.0 MPa. The VOCs concentration is 50-2000 ppm, preferably 200-1500 ppm, and more preferably 300-600 ppm. After treatment, the VOCs concentration in the atmosphere is lower than the VOCs emission limits for various industrial production processes.

[0021] Beneficial effects of this invention: 1. This invention achieves smaller single-phase CoMn2O4 spinel grain size by controlling powder particle size and calcination temperature, which further improves the specific surface area of ​​the active component and the mobility of oxygen species, thereby enhancing the activity of the catalyst powder.

[0022] 2. Before and after acid etching, the catalyst maintains the same phase structure and similar grain size. Acid / base etching successfully introduces a large number of oxygen vacancies into the catalyst, weakens the metal-oxygen bond strength, and significantly improves the spinel catalyst's ability to adsorb, activate, and transport oxygen species.

[0023] 3. Appropriate doping with alkali metals and rare earth metals can effectively modulate the low-temperature redox performance of CoMn2O4 spinel, further improving the catalyst activity. At the same time, different metals can be introduced as dopants according to the needs of the operating conditions to improve the catalyst selectivity.

[0024] 4. By coordinating three key parameters—sol viscosity, powder particle size, and dispersant dosage—the slurry maintains good dispersion of active substances at an appropriate viscosity, improving the mechanical stability of the coating and making the distribution of activation sites in the coating more uniform, thus preventing premature aggregation of active components that could affect catalytic activity.

[0025] 5. The negative pressure suction process can ensure uniform flow and coating of slurry within the honeycomb channels, resulting in high coating efficiency and good uniformity. Furthermore, the powder-slurry-negative pressure suction coating process can serve as a standardized preparation procedure. When different selective catalysts are required, the powder formulation can be directly adjusted, reducing the special requirements for the preparation process and equipment, which is beneficial for industrial applications. Attached Figure Description

[0026] Figure 1 This is a schematic diagram of the integral catalyst structure of the present invention. Detailed Implementation

[0027] The specific embodiments of the present invention will be further described below with reference to the accompanying drawings and technical solutions.

[0028] The monolithic catalyst for catalytic combustion of VOCs and its preparation method described in this invention specifically include the following steps: (1) Co salt and Mn salt precursors were mixed in a Co / Mn molar ratio of 1:2 using the sol-gel method, and a precipitant was added. The precipitate was dried and calcined to prepare a single-phase CoMn2O4 powder. (2) After acid / alkali etching treatment of single-phase CoMn2O4 powder, metal doping modification is performed, and after drying and calcination, modified CoMn2O4 catalyst powder containing one or more alkali metals and rare earth metals is prepared. (3) The modified CoMn2O4 catalyst powder, dispersant and prepared sol are mixed together. The resulting slurry is coated onto the overall carrier by negative pressure suction. The mixture is then dried and calcined to obtain the desired monolithic catalyst.

[0029] Specific preparation process of single-phase CoMn2O4 powder: Co and Mn salts were thoroughly mixed in ethanol, followed by the addition of a precipitant and stirring. The pH was adjusted to neutral, and the mixture was dried overnight at 300-500°C. o Calcination at C for 3-5 h. In the preparation of CoMn2O4, the Co salt precursor is one of cobalt acetate, cobalt nitrate, or cobalt chloride; the Mn salt precursor is one of manganese nitrate, manganese acetate, or manganese chloride. After preparation, acid / alkali treatment is performed to finally obtain a CoMn2O4 structure with high specific surface area and high VOCs catalytic combustion activity. The CoMn2O4 structure can be optimized by changing the types of precipitant, Co and Mn precursors, and synthesis conditions. Specific precursor / precipitant selections are shown in Table 1. The VOCs catalytic oxidation performance of some CoMn2O4 powder monolithic catalysts is shown in Table 2, where the colloid is alumina sol, and the monolithic support is cordierite honeycomb ceramic, as is the case for samples S1-S18 and D1-D21.

[0030] Table 1. Selection of different precursors, precipitants, and calcination procedures in the preparation of CoMn2O4 powder

[0031] Table 2. Catalytic oxidation performance of VOCs from some CoMn2O4 powder monolithic catalysts (T) 90 / o C)

[0032] The specific preparation process of CoMn2O4 powder modified by acid / base etching and metal doping: Sample S7 was selected for acid / alkali treatment. Acid treatment etched the CoMn2O4 surface, increasing its specific surface area to provide more oxygen activation sites; alkali treatment provided hydroxyl groups to CoMn2O4, improving its redox properties. The acid solution was selected from sulfuric acid, nitric acid, hydrochloric acid, or oxalic acid; the alkali solution was selected from sodium hydroxide or potassium hydroxide. The concentration of the acid / alkali solution was selected from 0.1-30 mol / L. The specific treatment process is as follows: Select the prepared CoMn2O4 powder, soak it in the prepared acid / alkali solution for 0.5-6 hours, then centrifuge and wash until neutral, dry overnight, and calcine in a muffle furnace at 300-600°C. oC, calcination time 2-6 h. The toluene catalytic oxidation performance of CoMn2O4 after partial acid / base treatment is shown in Table 3, where the toluene concentration is 500 ppm and the space velocity is 15000 h⁻¹. -1 .

[0033] Table 3. Acid / alkali treatment conditions and toluene catalytic oxidation performance of some CoMn2O4 powders.

[0034] To further improve the VOCs catalytic oxidation performance of CoMn2O4 powder catalyst, this invention incorporated metal doping into S7-1 of the aforementioned sample. The main effect of metal doping is to regulate the activity of oxygen species in the CoMn2O4 powder catalyst. One or more alkali metals and rare earth metals were added during the preparation of CoMn2O4 powder, and the effects of the type and ratio of dopant elements on the performance of the CoMn2O4 powder were investigated. Table 4 shows the overall catalytic oxidation performance of the CoMn2O4 powder catalyst corresponding to some dopant elements and their doping ratios, where the toluene concentration was 500 ppm and the space velocity was 15000 h⁻¹. -1 .

[0035] Table 4. Catalytic oxidation performance of toluene prepared by catalysts with partial doping elements and their doping ratios

[0036] Sol preparation process: An acid solution was added dropwise to a sol precursor suspension, with the acid-to-suspension ratio controlled at 4:1-1:10. After standing for 0.5-24 hours, a sol was obtained. The acid solution was selected from nitric acid, oxalic acid, or citric acid, with a concentration controlled at 0.1-10 mol / L. The sol precursor was selected from boehmite, γ-alumina, aluminum hydroxide, sodium silicate, or polyethylene glycol, with a suspension concentration controlled at 1-30 wt%. The selection of some raw materials for colloid preparation and their viscosity properties are shown in Table 5.

[0037] Table 5. Partial preparation of sols and their viscosity properties

[0038] Preparation of coating slurry: The CoMn2O4 powder D18 prepared above was ground and sieved to a particle size range of 0.04-0.3 mm. It was then added to different sols and thoroughly mixed. The powder addition amount was 1-20 wt%, along with 0.5-3 wt% dispersant. The mixture was then coated onto a support and dried and calcined overnight to obtain the desired monolithic catalyst. The calcination temperature was 300-600 °C. oC, the results are shown in Table 6. The monolithic catalyst obtained by combining CoMn2O4 powder and pseudoboehmite colloid in the above M2 sample exhibits a high To for the catalytic oxidation of toluene. 90 251 o C, where the toluene concentration is 500 ppm and the reaction space velocity is 15000 h⁻¹. -1 .

[0039] Table 6. Effects of powder particle size, feed amount, calcination temperature and sol type on toluene oxidation performance

[0040] Table 7. Effects of powder particle size, feed amount, calcination temperature and sol type on toluene oxidation performance

[0041] Further research was conducted on the effects of different acid-aluminum ratios of boehmite colloids and different amounts of CoMn2O4 powder on the viscosity of the coating slurry and the catalytic oxidation performance of toluene. The results are shown in Table 8. The amount of boehmite colloid was controlled between 1 and 20 wt%, and the acid-aluminum ratio in the colloid was controlled between 4:1 and 1:4.

[0042] Table 8. Effects of powder input amount and aluminum acid ratio on slurry viscosity and toluene oxidation performance.

[0043] Load of coating slurry on the overall carrier: This invention further explores the effects of suction pressure and slurry coating capacity on the overall performance of cordierite honeycomb ceramic catalysts. The process of preparing the overall catalyst using negative pressure suction is as follows: The coating slurry is placed in a container, and the square cordierite honeycomb ceramic carrier is placed in a closed negative pressure suction device. The lower half of the cordierite honeycomb ceramic is placed within the coating slurry. The suction device is turned on, allowing the coating slurry to rise from the bottom to the top of the cordierite honeycomb ceramic until it reaches the waste bottle. The coating slurry capacity is controlled at 10-100 mL, the suction pressure at 0.002-0.08 MPa, and the contact area between the square cordierite honeycomb ceramic and the coating slurry at 2-16 cm². 2 The number of suction cycles is controlled between 1 and 10. As shown in Table 9, preferably, the coating slurry volume is 20-50 mL, and the contact area is 4-8 cm². 2 .

[0044] Table 9. Catalytic oxidation performance of toluene prepared by partial negative pressure suction method

[0045] Different monolithic carriers, calcination temperatures, and loading rates significantly influence the growth of the coating slurry on the monolithic surface. Calcination temperature affects the interaction between the sol and CoMn2O4 powder; excessively high calcination temperatures can lead to agglomeration of substances in the slurry, and the size of these agglomerated particles directly affects catalyst activity. During the preparation of the monolithic catalyst, the calcination temperature is controlled between 300-600°C. o C, the load is controlled between 1-20 wt%.

[0046] Table 10 Effect of different calcination temperatures and loading rates on the catalytic oxidation performance of toluene

[0047] Catalysts prepared under different conditions in this invention were randomly selected for mechanical stability testing. The catalysts were placed in deionized water and sonicated at 60 Hz and 45 W for 1 hour, and their mass loss rate was then tested. Table 11 shows that the overall catalyst prepared in this invention exhibits strong mechanical stability, with mass loss rates after sonication all below 6‰.

[0048] Table 11. Mechanical stability tests of different samples

[0049] As can be seen from the test results of the above embodiments and comparative examples, the monolithic catalyst for catalytic combustion of VOCs and its preparation method described in this invention achieves good results at 500 ppm and 15000 h⁻¹. -1 Under the conditions, in 251 o C can achieve 90% conversion of toluene, and it is also very effective in treating other VOCs. The catalyst also has excellent mechanical stability and is suitable for industrial scale-up production.

[0050] The applicant declares that the above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.

Claims

1. A method for preparing a monolithic catalyst for the catalytic oxidation of VOCs, characterized in that, Includes the following steps: (1) Mix the two types of precursors, Co salt and Mn salt, at a Co to Mn molar ratio of 1:2 and then mix them thoroughly in excess ethanol. After mixing, the solid content is controlled at 100g / L-200g / L. Then, add the precipitant dropwise and stir thoroughly. After adjusting the pH to neutral, filter out the precipitate, wash it, and dry it at 80-120℃ for 2-3h. Then, calcine it at 300-400℃ for 3-5h to prepare a single-phase CoMn2O4 powder. (2) After acid etching of single-phase CoMn2O4 powder, metal doping modification was performed, and after drying and calcination, modified CoMn2O4 catalyst powder containing alkali metal and rare earth metal was prepared. (3) The modified CoMn2O4 catalyst powder, dispersant and sol are mixed in a mass ratio of (10-25):(0.5-3):(72-89.5) to prepare the final coating slurry. The coating slurry is coated onto the carrier by negative pressure suction, and then dried and calcined to obtain the desired monolithic catalyst. The monolithic catalyst comprises a cordierite honeycomb ceramic support and a cobalt-manganese composite oxide coating coated on the surface of the cordierite honeycomb ceramic support; the cobalt-manganese composite oxide coating contains spinel structure active components, with a thickness of 40-50 μm, and its mass ratio to the support is between 5% and 20%. The cobalt-manganese composite oxide coating further contains one or more alkali metals and one or more rare earth metals; the alkali metals and rare earth metals are modified on the cobalt-manganese composite oxide. The alkali metal is selected from one or more of K, Na, Li, Rb, and Cs; the rare earth metal is selected from one or more of La, Ce, Pr, and Nd; if the alkali metal is A and the rare earth metal is B, then the molar ratio of (A+B), Co, and Mn is (0.05-0.2):1:

2. The acid used for the acid etching is selected from one of sulfuric acid solution, nitric acid solution, hydrochloric acid solution, and oxalic acid solution, with an acid concentration of 0.1-30 mol / L and a processing time of 0.5-3 h; The Co salt precursor is one of cobalt acetate, cobalt nitrate, and cobalt chloride; the Mn salt precursor is one of manganese nitrate and manganese acetate; the precipitant is one of oxalic acid and sodium carbonate; the dispersant is one of CTAB cationic surfactant or P123 nonionic surfactant, accounting for 0.5-3 wt% of the total coating slurry. The sol is a pseudoboehmite sol, silica sol, silica-alumina sol, or phospho-alumina sol. The preparation steps of the sol are as follows: add sol powder to deionized water and stir for 5-30 min; the mass ratio of sol powder to water is 0.05-0.25:1 to obtain liquid A; add 1 mol / L concentrated nitric acid to deionized water and stir to mix thoroughly to obtain liquid B; the mass ratio of nitric acid to water is 0.15-0.5; mix liquids A and B at a mass ratio of 0.2-0.6:1, and let stand for 0.5-24 h to obtain the sol.

2. The preparation method according to claim 1, characterized in that, The coating method specifically involves immersing the lower 1 / 3 to 1 / 2 of the cordierite honeycomb ceramic in a coating slurry, and then uniformly coating it using negative pressure at a pressure of 0.02-0.04 MPa for 1-5 times. The coated integral catalyst is dried at 80-120℃ for 1-2 hours and calcined at 400-500℃ for 3-5 hours. The modified CoMn2O4 catalyst powder is added to a sol with a solid content of 10-25 wt% and uniformly mixed at 20-80℃ for 0.5-6 hours to obtain the coating slurry.

3. The use of the monolithic catalyst obtained by the preparation method according to claim 1 in the catalytic oxidation of VOCs in the atmospheric environment.

4. The use according to claim 3, characterized in that: A monolithic catalyst was added to the fixed-bed reactor, with toluene, xylene, acetone, and / or ethyl acetate as the reactant gases; the reaction volume hourly space velocity was 5000-25000 h⁻¹. -1 The reaction pressure is controlled at 0.1-1.0 MPa; the VOCs concentration is 50-2000 ppm.

Citation Information

Patent Citations

  • Coated low-temperature flue gas denitration catalyst, and preparation method and application thereof

    CN105126827A